PERAN KOMUNITAS ONLINE ‘SUARA DISKO’ DALAM MEMBANGUN BRAND AWARENESS MUSIK TAHUN 80AN MELALUI INSTAGRAM THE ROLE OF ONLINE COMMUNITY ‘SUARA DISKO’ IN BUILD A BRAND AWARENESS THROUGH 80’S MUSIC INSTAGRAM - Annisa Pramitasari; Dini Salmiyah Fithrah Ali (Jurusan Ilmu Komunikasi UTM, 2018)
The development of the community is currently getting forward and more of young people who have an interest in a thing that is similar and they began to build a community. Suara Disko. is a community that has a purpose to popularize the 80s music. With the evolve of social media makes Suara Disko ha s a media as Instagram to introduce their communities online. The purpose of this research is to find out how the role of online communities ‘Suara Disko ‘ in built a Brand Awareness through 80s music Instagram. This research using the qualitative method with approach case studies with indicator consists of four levels of Brand Awareness by Durianto that are Brand Recognition, Brand Unaware, Brand Recall, and Top Of Mind. Results of the study mentioned that the role of the community Suara Disko in built a Brand Awareness is by establishing the identity, provide the education, interaction with the followers, and become catchy by followers when considering which popularized back 80s music. Then to achieve the purpose of Suara Disko to popularize 80s music, Suara Disko is using Instagram to deliver activities in the form of visual and message.